Handedness and the Preference of the Visual Field in Face Perception - Démuthová, Slávka; Démuth, Andrej (European Scientific Journal, ESJ, 2018)
Face perception is tightly connected with the hemispherical dominance, and thus can be different in right-, left-handed and ambidextrous subjects. The study focuses on preferences for the left or the right visual field in face perception by testing the preference for the left or the right half of the chimeric face, which has been blended from half male and half female facial composite. The preference in evaluation process of the chimeric face has been studied on 2,207 participants (59.9% female; 6,8% left-handers and 6,5% ambidextrous; mean age = 24.08 years) with an emphasize on their handedness and sex. Chi-Square Test showed a significant preference (Asymp. sig = 0.000) for the left visual field in right-handed, but not in left-handed (Asymp. sig. = 0.072) and ambidextrous (Asymp. sig = 0.134) participants. The same results were gained also after evaluation for each sex separately with an exception for ambidextrous females. They preferred left visual field in face evaluation statistically significantly (Asymp. sig. = 0.022) more than the right. The suggestions for further research and limitations of the study are discussed.